Annual Report of the Rowan Tree Church, 1986-1987 - Rowan Tree Church (Minneapolis, MN: Rowan Tree Church, 1987, 1987)
The fifth Annual Report details issues with the previous management by the Board of Directors, particularly it President, and its critical impact on the functioning of the Church. For the first time, various members of the Church responsible for functional areas contributed to the writing, which fostered cohesiveness within this community and set the stage for Church’s future.
This digital asset was created from the original digital scans by Rev. Paul V. Beyerl and provided to the Valdosta State University Archives & Special Collections to be part of their Rowan Tree Church Periodicals Collection of the New Age Movements, Occultism, and Spiritualism Research Library. The Rowan Tree Church is an earth-based religion founded by Rev. Paul Beyerl, a Third Degree Initiate in the Alexandrian Tradition of Wicca, and incorporated on February 4, 1980 in Minneapolis, Minnesota. The church is now based in Kirkland, Washington with many communities throughout the United States and Canada. The roots of the Church extend back to 1976 which Rev. Beyerl began teaching Wicca, Astrology, and Herbalism out of his home. The Church's religion, The Tradition of Lothloriën, embraces inclusiveness and accepts all people regardless of faith, sexual orientation, race, or gender, a noted departure from early Alexandrian Wicca. The Tradition has elements of Herbalism, Astrology and Tibetan Buddhism in its structure, and is deeply rooted in its Mystery School, an in-depth study program that leads to Ordination, and the Hermit's Grove, its educational and publishing entity. Noted publications are The Unicorn, The Littlest Unicorn for children, and The Hermit’s Lantern.
Keywords: Rowan Tree Church--History; Rowan Tree Church--Appropriations and expenditures; Beyerl, Paul V., Rev., 1945-; Lothloriën (Wiccan sect); Mystery School of Lothloriën; Wicca--Study and teaching; Littlest Unicorn (Rowan Tree Church); Annual reports